Optimisation of biotechnological processes related to the cultivation of microalgae in photobioreactors for obtaining metabolites of industrial interest - Ibañez, Manuel Vicente (2023)
Fil: Ibañez, Manuel Vicente. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas; Argentina.